2012
DOI: 10.4049/jimmunol.1103156
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4a Exerts an Anti-Inflammatory Effect through Accelerated IRAK1 Degradation in Macrophages

Abstract: Induction of cyclin-dependent kinase (CDK) inhibitor gene p16INK4a into the synovial tissues suppresses rheumatoid arthritis in animal models. In vitro studies have shown that the cell-cycle inhibitor p16INK4a also exerts anti-inflammatory effects on rheumatoid synovial fibroblasts (RSF) in CDK activity-dependent and -independent manners. The present study was conducted to discern how p16INK4a modulates macrophages, which are the major source of inflammatory cytokines in inflamed synovial tissues. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…There is mounting evidence that the dysfunctional chondrocyte phenotype that emerges with aging and OA is characteristic of cellular senescence (McCulloch et al., 2017). While p16 INK4a is known to inhibit cellular proliferation with aging and senescence in many tissues, the lack of chondrocyte proliferation in vivo provides an opportunity to assess whether p16 INK4a plays a functional role in aging that is independent of cell cycle inhibition, as has been proposed in other physiological settings (Goel et al., 2017; Murakami et al., 2012). In this study, we found that p16 INK4a expression is an effective biomarker of chondrocyte dysfunction despite not being an essential mediator of age‐related or injury‐induced OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mounting evidence that the dysfunctional chondrocyte phenotype that emerges with aging and OA is characteristic of cellular senescence (McCulloch et al., 2017). While p16 INK4a is known to inhibit cellular proliferation with aging and senescence in many tissues, the lack of chondrocyte proliferation in vivo provides an opportunity to assess whether p16 INK4a plays a functional role in aging that is independent of cell cycle inhibition, as has been proposed in other physiological settings (Goel et al., 2017; Murakami et al., 2012). In this study, we found that p16 INK4a expression is an effective biomarker of chondrocyte dysfunction despite not being an essential mediator of age‐related or injury‐induced OA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vivo evidence suggests that the primary functional consequence of high p16 INK4a expression with aging is to limit the proliferation of specific cell types during homeostasis or in response to injury (Janzen et al., 2006; Krishnamurthy et al., 2006; Liu et al., 2011; Molofsky et al., 2006; Sousa‐Victor et al., 2014). Several groups, however, have suggested cell cycle independent effects of p16 INK4a and CDK4/6 inhibition (Goel et al., 2017; Murakami, Mizoguchi, Saito, Miyasaka & Kohsaka, 2012), and it is unclear whether reduced p16 INK4a expression can protect tissues from age‐related pathologies that are associated with the SASP but not with replicative failure.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Murakami et al . (2012) recently showed that p16 INK4a expression suppresses LPS‐induced production of IL‐6 in mouse and human macrophages.…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%
“…Taniguchi et al found that introduction of p16 in the synovial fibroblast cells with the help of adenoviral gene therapy led to the suppression of disease progression in an animal model of RA (Taniguchi et al, 1999). Murakami et al concluded that p16, an inhibitor of cell cycle progression, showed antiinflammatory effects on rheumatoid synovial fibroblasts and its upregulation led to inhibition of inflammatory cytokine production from the macrophages (Murakami et al, 2012). Ultimately, these findings indicate a protective role of p16 in the suppression of the disease progression of RA.…”
Section: Effects Of Snf5 Expressions On Proliferation and Apoptosis Omentioning
confidence: 99%
“…Pannus releases inflammatory mediators locally and is responsible for destruction of the affected joints. Hence, inhibition of pannus formation would suppress the progression of RA (Sherr and Roberts, 1995;Taniguchi et al, 1999;Nasu et al, 2001;Nonomura et al, 2001Nonomura et al, , 2006Nishida et al, 2004;Choi et al, 2005;Murakami et al, 2012).…”
Section: Introductionmentioning
confidence: 99%